Circadian patterns of plasma leptin, insulin and glucose concentration in the toad-headed lizard Phrynocephalus versicolor. Issue 6 (1st November 2016) - Ping, Xiaoge; Han, Dawei; Jiang, Zhigang; Li, Chunwang
Abstract: To understand the circadian rhythms of the glucose metabolism and related hormones in desert reptiles, we studied the daily changes in plasma leptin, insulin, and glucose in the toad-headed lizard, Phrynocephalus versicolor, in the semi-desert of the Alashan Plateau. Blood samples were obtained from groups of 20 lizards (about equal sex ratio for each group) at 4-h intervals throughout a 24-h period. Leptin, insulin, and glucose levels were determined using ELISA, RIA, and the glucose oxidase method, respectively. Ambient temperature and humidity were also measured when the blood samples were taken. We found that: (1) there was a significant difference in plasma leptin concentrations at different times of day; (2) no significant circadian rhythm could be measured for plasma insulin and glucose; (3) ambient temperature, humidity, and body condition had no significant effect on plasma leptin, insulin, and glucose levels; and (4) there were significant correlations between plasma glucose concentrations and leptin concentrations 8 h later, and between insulin concentrations and leptin concentration 8–12 h later. These results suggested that the secretions of leptin and insulin played an important role in glucose metabolism in reptiles in an arid environment.